Audit of communication: a critical evaluation of the effectiveness of organizational communication in Colombian Universities (2019)
The main objective of the present article is to show the investigation project “Communication audit model design for private universities in Quindío and Risaralda” progress. The methodological process settled the investigation as a qualitative study, aiming to get information, where the interview was also applied. The study has also allowed us to characterize the communication labor and obtain important information to design the communication audit model, in order to evaluate its effectiveness and contribution to organizational development